[eCritic] automated english essay grader for Philippine high schools using latent semantic analysis neural networks - Macabenta, Angel Ruin L.
eCritic is an automated English essay grader for Philippine high schools using Latent Semantic Analysis (LSA) and Artificial Neural Networks (ANN). It scores students' essays based on correct spelling, grammar usage, discourse, and content. In this way, grades automated by the system have a high correlation with that of the grades given by the teachers since these are the same criteria teachers take note of in grading their students' works. Grades automated by eCritic are made up of three modules - syntax, which includes spelling and grammar, discourse and content. ASpell and Language-Tools are existing Open Source programs utilized for the spelling and grammar components of the syntax module. For the discourse, which corresponds to the fluidity and continuity of thought between paragraphs, LSA and ANN are applied. LSA is said to be an effective technique in finding the correlation of words in a set of essays based on its content, thus proving that it can be used for the automation of essay grading. However, there is no existing system that utilizes LSA to evaluate the discourse structure of essays. Thus, the purpose of this paper is to present a system that incorporates the LSA approach in grading the discourse component of the essays. This is the first attempt to use LSA to grade the flow of ideas from one paragraph to another since it has always been used to grade the content of essays. To aid LSA, ANN is used to process the outputs of LSA and produce better results.